The mass of a millisecond pulsar - Jacoby, B.; Hotan, Aidan; Bailes, M.; Ord, Stephen; Kulkarni, S. (Institute of Physics Publishing, Inc., 2005)
We report on nearly two years of timing observations of the low-mass binary millisecond pulsar, PSR J1909-3744 with the Caltech-Parkes-Swinburne Recorder II (CPSR2), a new instrument that gives unprecedented timing precision. Daily observations give a weighted rms residual of 74 ns, indicating an extremely low level of systematic error. We have greatly improved upon the previous parallax and proper motion measurements of PSR J1909-3744, yielding a distance of 1.14 +0.04 −0.03 kpc and transverse velocity of (200 +7 −6) km s −1 . The system's orbital eccentricity is just 1.35(12)×10 −7 , the smallest yet recorded. Since their discovery, the masses of the rapidly rotating millisecond pulsars have remained a mystery, with the recycling hypothesis arguing for heavy objects, and the accretion-induced collapse of a white dwarf more consistent with neutron stars less than the Chandrashkar limit. Fortuitously, PSR J1909-3744 is an edge-on system, and our data have allowed the measurement of the range and shape of the Shapiro delay to high accuracy, giving the first precise determination of a millisecond pulsar mass to date, m p =(1.438±0.024) M☉. The mass of PSR J1909-3744 is at the upper edge of the range observed in mildly recycled pulsars in double neutron star systems, consistent with the the recycling hypothesis. It appears that the production of millisecond pulsars is possible with the accretion of less than 0.2 M☉.